2020
DOI: 10.3390/su12187329
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on User Experience with Online Education Platforms in China

Abstract: During the COVID-19 pandemic, social education has shifted from face to face to online in order to avoid large gatherings and crowds for blocking the transmission of the virus. To analyze the impact of virus on user experience and deeply retrieve users’ requirements, this paper constructs a reasonable evaluation index system through obtaining user reviews about seven major online education platforms before and after the outbreak of COVID-19, and by combining the emotional analysis, hot mining technology, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(159 citation statements)
references
References 28 publications
6
126
0
4
Order By: Relevance
“…Zimbardo states that today's youth, who are used to the digital world, and used to permanent interaction, multidimensionality, multifunctionality and speed, has difficulties with traditional forms of learning, which could be related to this study's information that the students with higher proficiency in ICT skills were more satisfied with online education than those with lower ICT skills. Although the transition to online teaching, on the one hand, is a great challenge for the learning process [7,41], on the other hand, these results indicate that it should be seen as a positive opportunity to change traditional learning methods and adapt to new educational needs [42]. Considering the relationship between students' estimated ICT skills and those needed for online education, this study shows that the students estimate their ICT skill level as being higher than is needed, so it is not surprising that they are mostly satisfied with the combination of classes online and in person.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zimbardo states that today's youth, who are used to the digital world, and used to permanent interaction, multidimensionality, multifunctionality and speed, has difficulties with traditional forms of learning, which could be related to this study's information that the students with higher proficiency in ICT skills were more satisfied with online education than those with lower ICT skills. Although the transition to online teaching, on the one hand, is a great challenge for the learning process [7,41], on the other hand, these results indicate that it should be seen as a positive opportunity to change traditional learning methods and adapt to new educational needs [42]. Considering the relationship between students' estimated ICT skills and those needed for online education, this study shows that the students estimate their ICT skill level as being higher than is needed, so it is not surprising that they are mostly satisfied with the combination of classes online and in person.…”
Section: Discussionmentioning
confidence: 99%
“…Although the current pandemic is encouraging the reformation of the current methods of existing teaching modes [7], based on the analysis of the collected data, it can be concluded that FSPE students have a satisfactory knowledge of ICT skills, and it can be said that their sustainability and adaptation to the new requirements of online teaching are not worrying. However, this questionnaire did not test advanced computer literacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Step2, the “other irrelevant comments” category is excluded here, and more than 20,000 comments are selected. The sentiment score was processed by the natural language processing tool SnowNLP [ 41 , 42 ], the sentiment value of each Weibo comment was obtained by quantification, and the results are shown in Figure 24 .…”
Section: Empirical Analysismentioning
confidence: 99%
“…The results show that the low exchange rate and the positive sentiment of online reviews from tourism websites have a positive impact on the number of tourists to Japan. Chen et al 15 , 16 used text mining and emotion analysis methods to implement the effect of online education under the epidemic situation. Also, the experience effect was studied from the perspective of user and platform.…”
Section: Literature Reviewmentioning
confidence: 99%